Comparative Study of 150 vs. 200 Units of Botulinum Toxin as Treatment for Vaginismus - Helmi, Zeena R. (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To comparatively evaluate the outcome of treatment with 150 versus 200 units (U) of botulinum toxin in achieving pain-free intercourse and relieving muscle contraction in order to allow gynecological examination.Methods In this comparative prospective observational study, 99 patients with vaginismus were treated with botulinum toxin injections from September 2016 to August 2021. Diagnosis and grading of vaginismus severity were assessed using a Female Sexual Function Index (FSFI) questionnaire. Under local or general anesthesia, botulinum toxin diluted with preservative-free saline (150 U and 200 U) was injected into, above, and below the right and left bulbospongiosus muscle and the lateral submucosal areas of the introitus and perineal body using an insulin syringe. Patients were recalled after 2 weeks, and the postoperative outcome was recorded using a similar preoperative questionnaire.Results Overall, the mean age of patients was 30.2 years. The baseline and clinical characteristics were comparable between the 2 groups (p > 0.05). Significant improvements were seen in the pain and anxiety scores of finger penetration, dilator use, intercourse, and cotton swab in individual groups. The intergroup comparisons between 150 U and 200 U of Botox were not statistically significant (p > 0.05).Conclusion Low-dose Botox (150 U) is equally effective as high dose Botox injections (200 U) in vaginismus patients. Therefore, Botox-150 U can be used to treat vaginismus as an alternative to high doses of the same substance.
Keywords: vaginismus; botulinum toxin; sexual pain; anxiety; pain treatment